Malaysian non-Arabic speaking learners' readiness in a virtual second language learning environment - Noorafini Kassim; Muhammad Sabri Sahrir; Tunku Badariah Tunku Ahmad (Universitas Pendidikan Indonesia, 2023)
Readiness is an important indicator of learners' willingness to engage productively in a virtual learning environment. Low readiness is believed to be the main reason behind virtual learning failure. The purpose of this present study is to investigate the effects of online readiness on learners’ learning satisfaction and performance in a virtual second language learning environment on a sample of 203 Malaysian Non-Arabic Speaking Learners using a cross-sectional survey. This study further explored which dimension of readiness is found to be the strongest predictor of their level of satisfaction and performance. Partial least square structural equation modeling (PLS-SEM) analysis examined the predictive relationships between readiness, satisfaction, and performance. The results proved that online readiness was statistically a significant predictor of their learning satisfaction and performance, indicating computer and internet self-efficacy in performing activities in the virtual learning environment as the strongest predictor. By identifying the most influential predictors, this groundbreaking study recognizes which key elements of the virtual learning environment language learners would need more to relish learning and achieve their goals. This study offers critical insights that have not been previously explored by conducting a comprehensive analysis of the factors influencing learning satisfaction and performance. The findings, therefore, highlight the paramount importance of assessing the readiness of online learners and their learning environment, providing valuable guidance for higher education institutions seeking to enhance the success of VLLE. In addition, this study sets a precedent for future research in the field. It underscores the need for ongoing efforts to improve virtual language learning environments to serve students’ needs better.